Pengaruh Effleurage Massase terhadap Intensitas Nyeri Punggung pada Ibu Hamil di Klinik Abi Ummi Dw Sarmadi Palembang Tahun 2021 - Umi Solekah; Mariyam Mariyam; Alvira Damayanti (KOLONI, 2022)
Back pain is one of the discomforts experienced by pregnant women in the third trimester. The action that is often recommended is back rub therapy / Effleurage Massage. The purpose of this study was to determine the effect of Effleurage Massage on the intensity of back pain in pregnant women at the Abi UMMI DW Sarmadi Clinic Palembang. The sample in this study were third trimester pregnant women at the Abi UMMI DW Sarmadi Palembang clinic, totaling 8 respondents. The data collection technique in this study is using Accidental Sampling. This type of research is an Analytical Survey using the Case Control method. Based on the univariate results it was found that the intensity of back pain in pregnant women before Effleurage Massage was carried out obtained an average value of 3.13. Meanwhile, for the intensity of back pain in pregnant women after the Effleurage Massage, the average value was 1.13. The results of the Non Parametric Wilcoxon Test obtained p_value (0.011) < α (0.05) then Ha was accepted and Ho was rejected, which means that there is an effect of Effleurage Massage on the intensity of back pain in pregnant women. From the results of the study it can be concluded that Effleurage Massage can reduce the intensity of back pain in third trimester pregnant women. It is hoped that the research location, namely the Abi UMMI DW Sarmadi Palembang Clinic, will apply Effleurage Massage to pregnant women who experience back pain. Keywords: Back Pain Intensity, Effleurage Massage, Third Trimester Pregnant Women